2006
DOI: 10.1111/j.1600-051x.2006.00960.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of the VectorTM‐system compared with conventional subgingival debridement in vitro and in vivo

Abstract: Using the Vector -system, root surfaces can be debrided as thoroughly as with conventional instruments. However, treatment is more time consuming than conventional debridement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 32 publications
2
21
0
1
Order By: Relevance
“…Moreover, ultrasonic scalers show a better accessibility to furcations and grooves (Oda et al 2004), and possess a cavitational activity, which has been considered effective for removal of plaque and endotoxins as the theoretical adjunct to the mechanical action of the instrument (Walmsley et al 1988); however, this could not be verified clinically (Petersilka & Flemmig 1999). In accordance with other investigations (Braun et al 2006), ultrasonic debridement revealed a significant reduction of Pg , Pi , Tf , and Td as well as of the amount of all five bacteria in the present study; additionally, the detectable values of the more‐resistant Aa were significantly decreased after 3 months. For the red complex species, significant differences compared with baseline values could be shown even for the 6‐month evaluation.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, ultrasonic scalers show a better accessibility to furcations and grooves (Oda et al 2004), and possess a cavitational activity, which has been considered effective for removal of plaque and endotoxins as the theoretical adjunct to the mechanical action of the instrument (Walmsley et al 1988); however, this could not be verified clinically (Petersilka & Flemmig 1999). In accordance with other investigations (Braun et al 2006), ultrasonic debridement revealed a significant reduction of Pg , Pi , Tf , and Td as well as of the amount of all five bacteria in the present study; additionally, the detectable values of the more‐resistant Aa were significantly decreased after 3 months. For the red complex species, significant differences compared with baseline values could be shown even for the 6‐month evaluation.…”
Section: Discussionsupporting
confidence: 93%
“…A series of articles have compared the Vector system with hand scaling of teeth both in vitro and in vivo (Braun et al 2003, 2005a, b, 2006). The clinical studies follow a similar pattern in that they have used four variables (1) hand instrumentation with Gracey curettes, (2) a traditional ultrasonic system (US) (3) Vector with hydroxyl apatite (VHA) polishing fluid and (4) Vector with a silicon carbide (VSC) containing abrasive fluid.…”
Section: Discussionmentioning
confidence: 99%
“…The Vectorä system is recommended for use in conjunction with irrigation fluids containing hydroxyapatite or silicon carbide. Although this system removes calculus efficiently (Braun et al, 2002), the efficiency of removal is dependent on the abrasive fluid used.…”
Section: Ultrasonic Instrumentsmentioning
confidence: 99%